Brown bast control using rejuvenator to improve yield of Hevea brasiliensis Müll.Arg. - Nik Hashim, Nik Hashyati (2019)
Rubber tree (Hevea brasiliensis) is an important industrial crop, natural rubber representing almost half of the total world rubber production (47% in 2018). As in other crops, various plant physiological conditions and pathogenic diseases influence rubber production. Brown bast is one of the most serious threats to natural rubber production. Brown bast is an issue very specific to rubber tree, resulting the reduction of latex flow. It is now admitted as physiological disorder resulting from abiotic stress. Thus, the Rejuvenator is formulated based on macro- and micro- nutrients to treat this problem. This study focuses on brown bast control by application of Rejuvenator and H-plus to improve yield of Hevea brasiliensis. This experiment was conducted at Kuala Nal, Kelantan (5.595077ºN, 102.1564ºE). Split plot design and Randomized Completely Block Design (RCBD) was used as the experimental design with three replications. The objective of the first experiment was to determine the effect of various rates of concentration and frequency of Rejuvenator application to treat brown bast on Hevea brasiliensis. The treatments used were Rejuvenator concentration (0, 5, 10 and 15 g/L) and treatment frequency (every 3 days and every 6 days). Treatment 10 g/L of Rejuvenator concentration with every 6 days application resulted in the highest nutrient content, bark moisture content, latex yield and percentage of brown bast recovered. But these parameters were not significantly different from treatment 5, and 15 g/L of Rejuvenator concentration. Thus, treatment 5 g/L was recommended to make more cost effective. The objective of the second experiment was to evaluate the effect of H-plus application on latex productivity following Rejuvenator treatments. The brown bast treated tree was selected from the first experiment to apply in the second experiment. Three methods of H-plus application were applied to the brown bast treated trees were labeled as A1: panel application, A2: lace application and A3:control. Panel application (A1) showed the highest result in latex yield production (6.56 g/tree). However, there was no significant different between A1 and A2. Thus, any method of H-plus application can be practice by smallholder. Rejuvenator and H-plus treatment can be used to control brown bast syndrome and give higher result in latex yield. Thus, the suitable concentration and frequency of Rejuvenator application were established at 5 g/L in every 6 days and H-plus treatment application can be practiced by smallholder to maintain the latex production.